REMOVAL OF NICKEL (II) AND CADMIUM (II) IONS FROM WASTEWATER BY PALM FIBERS - ASMA BOUDAOUD; MEBROUK DJEDID; MOKHTAR BENALIA; CHIFAA AD; NASSIRA BOUZAR; HICHAM ELMSELLEM (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The palm fibers powder (PFP) was evaluated for the selective removal of nickel (Ni) and cadmium (Cd) from wastewater. The adsorbent was characterized by means of Fourier transform infrared spectrophotometer (FT-IR), X-ray diffraction (XRD) and polarized light microscopy (POM) measurements. The adsorption process was found to be highly pH dependent, facilitating selective adsorption of metals tested. The best Ni (II) and Cd (II) adsorption occurred at an initial concentration of 100 mg‧L-1, 1 g doses of PFP, a temperature of 20 °C, and pH = 5, 6.5 respectively. The maximum sorption capacities obtained with PFP for the studied metal ions were 6.81 mg‧g-1 for Cd (II) at 60 min and 4.42 mg‧g-1 for Ni (II) at 45 min. The adsorption is best fitted in Freundlich isotherm. A comparison of kinetic models (pseudo first-order and the pseudo second-order) at different conditions showed that the pseudo second-order kinetic model correlate the experimental data well. Van’t Hoff equation was used to evaluate the thermodynamic parameters (ΔH°, ΔS°, and ΔG°), which indicate that adsorption process is exothermic in nature, with the absolute values of ΔH° in range of 20-50 kJ‧mol-1 for the two metal ions and the values of ΔS° are found to be -0.142 and -0.062 kJ‧mol-1 for Cd (II) and Ni (II) ions respectively.